The relationship of the carriership of allelic variations in rs2228145 (A > C) of theIL6R gene with the levels of VCAM1 and ICAM1 gene transcripts in patients with essential hypertension - L. V. Topchieva; V. A. Korneva; I. V. Kurbatova (Вавиловский журнал генетики и селекции, 2020)
The levels of plasma interleukin 6 and its soluble receptors were found to be elevated in subjects with cardiovascular diseases, which points to amplification of the IL-6-mediated trans-signaling pathway in cells and the development of chronic inflammation. The allelic variation in the rs2228145 IL6R gene is associated with a change in the contents of the soluble and membrane-bound receptor forms mediating the biological activity of IL-6. Cytokine IL-6 is involved in the development of endothelial dysfunction by regulating the expression of the VCAM1 and ICAM1 genes, encoding intercellular adhesion molecules. Prior to this work, no data on the association of essential arterial hypertension (EAH) with rs2228145 allelic variations of the IL6R gene have been reported. The aim of our work was to study the relationship of the carriership of rs2228145 (A > C) allelic variations with the development of EAH and the VCAM1 and ICAM1 transcript levels. We analyzed samples of DNA isolated from the whole blood of 148 healthy donors and 152 patients with EAH (stages I-II). The genotyp-ing was performed by PCR-RFLP. The level of transcripts in peripheral blood leukocytes (PBL) was assessed by real-time PCR. Differences in the frequency distributions of rs2228145 (A > C) genotypes between the control group and the group of patients with EAH (χ2 = 9.303) were found. The frequency of the CC genotype in EAH patients was higher than in healthy people (0.191 and 0.095, respectively). The risk of EAH (I-II stages) development was shown to be 2.3 times higher in CC genotype carriers as compared to individuals with other genotypes (OR = 2.257, 95 % confidence interval 1.100-4.468). The levels of VCAM1 and ICAM1 gene transcripts in PBL of patients with EAH were significantly higher than in healthy people. The level of ICAM1 gene transcripts was almost 4 times higher in patients with CC genotype. The Kruskal-Wallis analysis of variance revealed an effect of rs2228145 (A > C) genotype on the transcriptional activity of ICAM1, which argues for its role in the pathogenesis of endothelial dysfunction and essential hypertension.